Antibacterial Activity of Ethyl Acetate Fraction of a Vicious Combination of Glass and Binahong Against Gram-Negative and Gram-Positive Bacteria Causing Diabetic Ulcers - Mitra Amalia; Tiara Dini Harlita; Ganea Qorry Aina (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aimed to evaluate the antibacterial activity of the ethyl acetate fraction combination of Strobilanthes crispa and Anredera cordifolia leaves against Gram-positive and Gram-negative bacteria causing diabetic ulcers, namely Staphylococcus aureus, Klebsiella pneumoniae, and Pseudomonas aeruginosa. It was hypothesized that the 1:1 combination at 75% concentration would inhibit bacterial growth due to its secondary metabolite content. Research Method: This true experimental study used a one-factor Completely Randomized Design. Antibacterial testing was conducted in vitro using the Kirby-Bauer disc diffusion method on Mueller-Hinton Agar with a 1:1 combination at 75% concentration, Ciprofloxacin 5 μg as a positive control, and sterile aquadest as a negative control. Data were analyzed using Shapiro-Wilk, One-way ANOVA, and Duncan Multiple Range Test. Phytochemical screening was also performed. Results and Discussion: The combination extract showed mean inhibition zones of 10.7 mm against S. aureus, 8.8 mm against K. pneumoniae, and 8.1 mm against P. aeruginosa. The inhibition response was strong against S. aureus and moderate against the two Gram-negative bacteria. Phytochemical screening identified flavonoids, steroids, and tannins in the combination extract. Implications: The findings indicate that the extract combination has potential as a natural antibacterial candidate against diabetic ulcer pathogens, although its effectiveness remains below that of Ciprofloxacin. Further in vivo toxicity studies and quantitative phytochemical analyses are needed.